2018
DOI: 10.1016/j.clbc.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Weight Gain During Adjuvant Endocrine Therapy and Association of Such Weight Gain With Recurrence in Long-term Breast Cancer Survivors

Abstract: Premenopausal BC patients had an increased risk of weight gain after 5 years of ET; however, BC patients with a weight gain of > 5% did not have an increased risk of disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 74 publications
5
35
1
2
Order By: Relevance
“…Our results support previous studies that have found slightly overweight women might maintain a better QOL or observe less QOL changes, than their normal, obese, or even non-cancer counterparts[11]. Our results also support previous studies that found only slight weight gains over time with no association with age[4]. There is also the possibility that participants adjusted to their health status changes over the seven years of participation and thus only small changes in their QOL were reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support previous studies that have found slightly overweight women might maintain a better QOL or observe less QOL changes, than their normal, obese, or even non-cancer counterparts[11]. Our results also support previous studies that found only slight weight gains over time with no association with age[4]. There is also the possibility that participants adjusted to their health status changes over the seven years of participation and thus only small changes in their QOL were reported.…”
Section: Discussionsupporting
confidence: 92%
“…Weight gain is a potential negative outcome of breast cancer treatment, occurring in 50% to 96% of breast cancer patients[3]. More recently, Raghavendra et al[4] found that 33.7% of 1281 long-term survivors in their study gained more than 5% of their pre-treatment weight after 5 years of endocrine therapy. That said, the amount of weight gain and reasons for it remain inconsistently reported in the literature[5-9].…”
Section: Introductionmentioning
confidence: 99%
“…Our results highlighted that younger survivors and women with a higher BW before diagnosis were more likely to have gained weight five years later. This echoes findings in other surveys [46,47]. We also found a significant association between weight gain and lymphedema.…”
Section: Body Weight Evolutionsupporting
confidence: 90%
“…Schvartsman et al found age differences related to weight changes during adjuvant chemotherapy, where women over 50 years old were more likely to lose weight during adjuvant chemotherapy, whereas women under 30 years old gained weight (8). In one study, Asian women had the lowest risk of weight gain post breast cancer diagnosis (5).…”
Section: Introductionmentioning
confidence: 99%